Tying algorithm for linking of finite element meshes with different degrees of refinement. Application to finite element analyses of tires - Liu, Changhong; Meschke, Gunther; Helnwein, Peter; Mang, Herbert A. (Computer Assisted Methods in Engineering and Science; Vol 2 No 4 (1995), 2023)
A tying algorithm for the linking of two originally geometrically incompatible finite element meshes with different degrees of refinement is proposed. It is characterized by the enforcement of geometric continuity between the two meshes at their common boundary and by specification of displacement constraints for the nodes located on this boundary. The two-dimensional as well as the three-dimensional case is considered. The proposed tying algorithm is applied to finite element analysis of the model of an automobile tire with a simplified tread profile. Consideration of this tread profile is restricted to the anticipated region of contact of the tire with the road surface and to its vicinity. For the remaining part of the analysis model a coarser finite element mesh is used. The tying algorithm is also applied to the generation of a finite element mesh with a realistic tread geometry in the aforementioned region.